Diseño y montaje de un sistema de bombeo con capacidad de 0,27 Litros/s para uso agrícola (bebederos de ganado y riegos) de la Finca Villa Norma, San Vicente del Caguán (2022)
The department of Caquetá currently has in rural areas; problems to supply water by the current aqueducts, causing ponds for their own agromost farms to draw water from rivers and natural storage industrial supply. Based on this need, the Villa Norma farm located in San Vicente, was given a solution through the design and installation of a pumping system with a capaci ty of 0.27 liters / s for drinking and irrigation requirements. With a practical empirical methodology, turbid water was transferred from a distance of 230,000 mm; using a 1 Hp pump. To reduce the turbidity of the water, a configuration of tanks with filte ring layers of stone, pebbles, charcoal and sand was used. Allowing, to distribute the water by gravity, due to a height difference of 8000 of 3000 liters. mm in the storage area